PERCEIVED ORGANIZATIONAL SUPPORT : PENGARUHNYA TERHADAP TURNOVER INTENTIONS - Maryam Rozana; Retno Dwiyanti (PSIMPHONI, 2022)
This study aims to examine the effect of perceived organizational support on turnover intentions. The sample of this study amounted to 95 subjects. The data collection method in this study used the Perceived Organizational Support Scale, and the Turnover Intentions Scale. The data analysis technique used is to test the outer model and inner model using the SmartPLS 3.0 software. The results of the analysis show that There is an influence of perceived organizational support on turnover intentions as indicated by a T-value of 2.643 and a statistic of 2.643. P-Value 0.008. In this study, the conditions for convergent validity, discriminant validity and reliability were met. In conclusion, there is an effect of perceived organizational support on turnover intentions.